ANALYSIS OF STUDENTS' MATHEMATICAL PROCEDURAL FLUENCY IN ALGEBRAIC OPERATIONS MATERIAL IN TERMS OF METACOGNITION - Risda Pratama Damayanti; Supratman Supratman; Diar Veni Rahayu (Math Educa Journal, 2025)
This study seeks to examine students' mathematical procedural fluency in addressing algebraic operation problems through the lens of metacognition. The research is qualitative in nature and employs an exploratory methodology. The instruments utilized in this study include mathematical procedural fluency assessments, metacognitive questionnaires, and interviews. The participants comprised three students from class VII of SMP Muslimin Samarang, each demonstrating fluent criteria in mathematical procedural fluency. The findings revealed that despite sharing the same procedural fluency criteria, the subjects exhibited varying metacognitive criteria: subject S1 displayed strong metacognitive criteria, subject S2 showed moderately strong metacognitive criteria, and subject S3 exhibited weaker metacognitive criteria. Several alternative strategies can be implemented to enhance learning and foster procedural fluency in relation to metacognition, including the use of diverse learning models, the development of instructional materials, the creation of culturally relevant questions, and the incorporation of engaging learning media.